2021
DOI: 10.3233/cbm-200072
|View full text |Cite
|
Sign up to set email alerts
|

SATB-1 and Her2 as predictive molecular and immunohistochemical markers for urothelial cell carcinoma of the bladder

Abstract: Studying bladder cancer molecular biology revealed the presence of genetic alterations. So, detection of molecular biomarkers that help in monitoring the disease, evaluating the prognosis of the patients, and their response to therapy is needed. In this study, we investigated the expression and the prognostic significance of SATB-1 and ERBB2 mRNA and protein by quantitative RT-PCR and immunohistochemical analysis in urothelial bladder cancer cases and the surrounding normal bladder tissue. The correlations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…According to our study, a significant difference was observed in the percentage of HER2+ among different clinical stages of UC ( p = 0.019) ( Table 2 ). This finding is consistent with another research study, which demonstrated a strong association between elevated levels of HER2 and the stage of UC at both mRNA and protein levels ( p < 0.001) ( Hussein et al, 2021 ). It is worth noting that HER2 overexpression is considered an early event in urothelial tumor development and rarely occurs during subsequent tumor progression.…”
Section: Discussionsupporting
confidence: 93%
“…According to our study, a significant difference was observed in the percentage of HER2+ among different clinical stages of UC ( p = 0.019) ( Table 2 ). This finding is consistent with another research study, which demonstrated a strong association between elevated levels of HER2 and the stage of UC at both mRNA and protein levels ( p < 0.001) ( Hussein et al, 2021 ). It is worth noting that HER2 overexpression is considered an early event in urothelial tumor development and rarely occurs during subsequent tumor progression.…”
Section: Discussionsupporting
confidence: 93%
“…BCa expresses multiple tumor-associated antigens, suggesting favorable conditions for CAR T cell therapy. Many pan-cancer tumor targets, including human epidermal growth factor receptor 2 (HER2), mucin 1 (MUC1), and EGFR, are also expressed at high levels in UCs and may serve as therapeutic targets [50,51]. One current ongoing clinical trial targets HER2 (NCT03740256).…”
Section: Car T Cell Therapy In Bcamentioning
confidence: 99%
“…Elevated mRNA and protein levels of both genes were significantly associated with tumor stage and lymph node involvement. These findings suggest that SATB1 and ERBB2 may serve as potential biomarkers for predicting the aggressive behavior and poor prognosis of bladder cancer [ 101 ]. In NMIBC tissues, both the mRNA and protein expression of SATB1 was significantly upregulated as compared to that of adjacent normal tissues.…”
Section: Homeobox Genes In Bladder Cancermentioning
confidence: 99%